Lactate Level as a Prediction Factor of Reperforation after Repairing Gastric Perforation - Budipramana, Vicky Sumarki (Folia Medica Indonesiana, 2019)
Reperforation after gastric perforation repair is a complication which increases the rate of morbidity and mortality in gastric perforation. The lack of ability of the tissue to use oxygen in septic condition causes anaerobic cellular metabolism and furthermore it will cause failure in closing the perforation. The production of anaerobic metabolism is lactic acid which can be measured from the blood. The aim of this study is to determine the cut-off point of blood lactate level as a predictor of reperforation after repairing gastric perforation. Forty-six patients diagnosed as gastric perforation, who were repaired in Dr Soetomo Hospital from October 2014 to October 2015 were recruited as samples. Serum lactate was taken one hour before repairing the perforation. After being repaired, the patients were observed until the 14th day to evaluate whether any reperforation would occur or not . The design of this research was cross-sectional, analytic observational. The data was analyzed using independent t-test and ROC for obtaining the cut-off point as a predictor of the reperforation after the gastric perforation was repaired. There was a significant difference in the mean of lactate level in the group with reperforation compared with that of the non-reperforation group, that is as big as 3.74±0.59 mmol/L and 2.60±0.76 mmol/L. Using ROC curve analysis, there was the cut-off point of lactate level for reperforation 3.35 mmol/L, with sensitivity 92.9%, specificity 84.4%, positive predictive value 72% and negative predictive Value 96.4%, accuracy 87.0% and in the AUC value 0.902.